The multiple process model of goal-directed reaching revisited. (January 2017) - Elliott, Digby; Lyons, James; Hayes, Spencer J.; Burkitt, James J.; Roberts, James W.; Grierson, Lawrence E.M.; Hansen, Steve; Bennett, Simon J.
Highlights: Aiming movements prepared to optimize speed, accuracy and energy. Prior knowledge about feedback important for limb regulation. Two types of online regulation: impulse control and limb-target control. Differences between multiple process model and other models. Abstract: Recently our group forwarded a model of speed-accuracy relations in goal-directed reaching. A fundamental feature of our multiple process model was the distinction between two types of online regulation: impulse control and limb-target control. Impulse control begins during the initial stages of the movement trajectory and involves a comparison of actual limb velocity and direction to an internal representation of expectations about the limb trajectory. Limb-target control involves discrete error-reduction based on the relative positions of the limb and the target late in the movement. Our model also considers the role of eye movements, practice, energy optimization and strategic behavior in limb control. Here, we review recent work conducted to test specific aspects of our model. As well, we consider research not fully incorporated into our earlier contribution. We conclude that a slightly modified and expanded version of our model, that includes crosstalk between the two forms of online regulation, does an excellent job of explaining speed, accuracy, and energy optimization in goal-directed reaching.